The potential of low-cost UAVs and open-source photogrammetry software for high-resolution monitoring of alpine glaciers: A case study from the kanderfirn (Swiss Alps) - Groos, Alexander R.; Bertschinger, Thalia; Kummer, Céline; Erlwein, Sabrina; Munz, Lukas; Philipp, Andreas (Geosciences, 2019)
Unmanned Aerial Vehicles (UAV) are a rapidly evolving tool in geosciences and are increasingly deployed for studying the dynamic processes of the earth's surface. To assess the potential of autonomous low-cost UAVs for the mapping and monitoring of alpine glaciers, we conducted multiple aerial surveys on the Kanderfirn in the Swiss Alps in 2017 and 2018 using open hardware and software of the Paparazzi UAV project. The open-source photogrammetry software OpenDroneMap was tested for the generation of high-resolution orthophotos and digital surface models (DSMs) from aerial imagery and cross-checked with the well-established proprietary software Pix4D. Accurately measured ground control points served for the determination of the geometric accuracy of the orthophotos and DSMs. A horizontal (xy) accuracy of 0.7-1.2 m and a vertical (z) accuracy of 0.7-2.1 m was achieved for OpenDroneMap, compared to a xy-accuracy of 0.3-0.5 m and a z-accuracy of 0.4-0.5 m obtained for Pix4D. Based on the analysis and comparison of different orthophotos and DSMs, surface elevation, roughness and brightness changes from 3 June to 29 September 2018 were quantified. While the brightness of the glacier surface decreased linearly over the ablation season, the surface roughness increased. The mean DSM-based elevation change across the glacier tongue was 8 m, overestimating the measured melting and surface lowering at the installed ablation stakes by about 1.5 m. The presented results highlight that self-built fixed-wing UAVs in tandem with open-source photogrammetry software are an affordable alternative to commercial remote-sensing platforms and proprietary software. The applied low-cost approach also provides great potential for other regions and geoscientific disciplines.
Created from Fastlane, Scopus look-up
Keywords: Digital elevation models; Glacier dynamics; Glacier monitoring; OpenDroneMap; Orthophotos; Paparazzi UAV; Photogrammetry; Structure from motion; Unmanned Aerial Vehicles